Doa Ibu Kami; Kajian Kristologi Feminis - Patty, Brayen Aliong (IAKN Ambon, 2023)
Humans live and develop in accordance with the development of civilization in their lives. Integrated Christianity as an integral part of human life also undergoes changes according to its civilization. This change that does not change the immanent basic substance is a form of Christian growth that follows the opportunities and challenges of the times. One of the integral elements of Christianity is Christology. Christology is a means for humans to know and consider the nature of God. This is born from struggles and experiences, one of which is the subordination of women. The embodiment of this doctrinal concept is expected to be able to become a church system that pays attention to universally, the existence of the people in an equal position.